ANALISIS NERACA MASSA DAN ENERGI PRENEUTRALIZER PRODUKSI PUPUK NPK - Fina Syafaatul Udzmah Suparman; Zainal Mustakim; Faridz Zainuddin Novianto (Journal of Industrial Engineering & Technology Innovation, 2026)
The preneutralizer unit is one of the important stages in the NPK fertilizer production process, functioning as the initial reactor for slurry formation through the netralization reaction between ammonia, sulfuric acid, and phosphoric acid. The reaction is exothermic and affects the energy distribution and operating conditions of the system. This study aims to analyze the mass and energy balance of the prenetralizer unit ini the NPK fertilizer production process based on actual operating data under steady-state conditions. The calculations were carried out by considering the mass flow rate of raw materials, material purity, water content, reaction stoichiometry, sensible enthalpy changes, and heat of reaction during the process. The mass balance result showed that the total mass entering and leaving the system was balance at 31,040 kg/h without mass accumulation. In additon, the exothermix heat of reaction became the largest energy contribution in the system, reaching 12,488,557.77 kJ/h. the main products formed were ammonum sulfate and monoammonium phosphate. The result indicate that the mass and energy balance approach can be used to evaluate the performance of the preneutralizer unit in the NPK fertilizer.